Molecular Features Underlying Selectivity in Chicken Bitter Taste Receptors - Di Pizio, Antonella; Shy, Nitzan; Behrens, Maik; Meyerhof, Wolfgang; Niv, Masha Y. (Frontiers in Molecular Biosciences, 2018)
Chickens sense the bitter taste of structurally different molecules with merely three bitter taste receptors (Gallus gallus taste 2 receptors, ggTas2rs), representing a minimal case of bitter perception. Some bitter compounds like quinine, diphenidol and chlorpheniramine, activate all three ggTas2rs, while others selectively activate one or two of the receptors. We focus on bitter compounds with different selectivity profiles towards the three receptors, to shed light on the molecular recognition complexity in bitter taste. Using homology modeling and induced-fit docking simulations, we investigated the binding modes of ggTas2r agonists. Interestingly, promiscuous compounds are predicted to establish polar interactions with position 6.51 and hydrophobic interactions with positions 3.32 and 5.42 in all ggTas2rs; whereas certain residues are responsible for receptor selectivity. Lys3.29 and Asn3.36 are suggested as ggTas2r1-specificity-conferring residues; Gln6.55 as ggTas2r2-specificity-conferring residue; Ser5.38 and Gln7.42 as ggTas2r7-specificity conferring residues. The selectivity profile of quinine analogs, quinidine, epiquinidine and ethylhydrocupreine, was then characterized by combining calcium-imaging experiments and in-silico approaches. ggTas2r models were used to virtually screen BitterDB compounds. ~50% of compounds known to be bitter to human are likely to be bitter to chicken, with 25%, 20%, 37% predicted to be ggTas2r1, ggTas2r2, ggTas2r7 agonists, respectively. Predicted ggTas2rs agonists can be tested with in-vitro and in-vivo experiments, contributing to our understanding of bitter taste in chicken and, consequently, to the improvement of chicken feed.